Multiple Myeloma with Plasmacytoma of the Lung - A Rare Entity (Journal of Medicine, 2022)
Multiple myeloma is a malignant proliferation of plasma cells that typically presents in the bone marrow.Extramedullaryplasmacytoma (EMP) represents an unusual and characteristically progressive malignancythat can arise outside the bone marrow. The occurrence of multiple myeloma with plasmacytoma of thelung is very unusual. Herein, we report a case of multiple myeloma with plasmacytoma of the lungdiagnosed by CT-guided FNAC and bone marrow trephine biopsy.J MEDICINE 2022; 23: 96-100